Extracavitary primary effusion lymphoma: clinical, morphological, phenotypic and cytogenetic characterization using nuclei enrichment technique. Issue 5 (19th August 2014) - Juskevicius, Darius; Dietsche, Tanja; Lorber, Thomas; Rufle, Alexander; Ruiz, Christian; Mickys, Ugnius; Krasniqi, Fatime; Dirnhofer, Stephan; Tzankov, Alexandar
Abstract : Abstract Aims: Primary effusion lymphoma (PEL) is a rare form of aggressive B‐cell lymphoma, which typically manifests as malignant effusion in the body cavities. However, extracavitary solid variants are also described. The aim of this study was to investigate copy number aberrations in two cases of solid PEL at their first occurrences and relapse by applying a newly developed methodology of tumour nuclei enrichment. Methods and results: Using histological and genetic techniques, a novel protocol for tumour nuclei enrichment by flow sorting and array‐comparative genomic hybridization, we characterized two cases of extracavitary PEL, one of which later relapsed as effusion. Both primary tumours were positive for HHV8 and EBV, confined to lymph nodes, and aberrantly expressed CD3, yet displaying clonal immunoglobulin gene rearrangements indicating B‐cell origin. Cytogenetic characterization of primary tumours revealed modest number of aberrations, partially overlapping with previously reported affected loci. The effusional relapse in case 1 was cytogenetically related to the primary tumour but showed dramatic increase of chromosomal instability. Conclusions: We for the first time demonstrate a cytogenetic relationship between solid and effusional presentations of PEL. Moreover, we provide an indirect evidence of multiple malignant clones, which gave rise to clonally‐related, yet karyotypically different relapsing lymphoma manifestations.